Reconfigurable Metasurface of Magnetoplasmonic Microbundle Array for Chiral Signal Enhancing. Issue 4 (15th December 2022) - Gwak, Juyong; Nguyen, Huu‐Quang; Jeong, Ki‐Jae; Kim, Youngmi; Park, Se Jeong; Choi, Youngeun; Goddati, Mahendra; Tufa, Lemma Teshome; Tang, Zhiyong; Lee, Jaebeom
Abstract: Novel design of flexible chiral metasurface has been attractive to control electromagnetic dynamics for fabricating integrated enantiomeric sensing devices. In this article, a reconfigurable metasurface decorated with planar magnetoplasmonic microbundle arrays of Au@Fe3 O4 core‐shell nanowires (NWs) on polydimethylsiloxane film is fabricated. Its chiroptical property is willingly manipulated by skew angle (θ), that is, the angle between applied magnetic field vector (B ) and tangent vector (T ) of a curved metasurface. Interestingly, the as‐prepared NW metasurface presents many internal skew angles (θin ) among respective NWs at nanoscale as well as additional external skew angle (θex ) among arrays at microscale, extraordinarily enhancing chiroptical signal compared to other nanosphere or single NW arrays where lack of θin is observed. Computational simulation proves the disruption of the symmetry via distinct θin and θex of the aligned microbundle array. In addition, the optical chirality induced by θin could be analysed by magnetic circular dichroism (MCD). These results suggest a strategy to implement spectacle lenses with circular polarizer capabilities and the fabricated metafilm specifically modulates the absorption of circularly polarized light and can become a novel universal means to produce flexible devices for further signal enhancing at nanoantennas and biosensors. Abstract : A reconfigurable metasurface with magnetoplasmonic microbundle arrays demonstrates controllable and flexible chiroptical properties. This chiroptical property is manipulated by two kinds of skew angles regarding bundle structure, applied magnetic field vector (B) and tangent vector (T) of a curved metasurface. The reconfigurable microbundle array metasurface suggests a strategy to implement spectacle lenses with circular polarizer capabilities.